Criminal Crime Policy against Child Pornography (Perspective Protection of the Rights of the Child Pornography Victims of Crime) - Hakim, Lukman (2014)
At the UU. 44 Year 2008 on Pornography gives special attention to children who are prone to be involved in pornography a criminal offense. Given the current storm pornography carries a high crime escalation including its effect on children, it is necessary to study and carried out with the aim to: 1) understand the forms of legal protection that is applied to the crime of child pornography involved, 2) analyze the Criminal Policy against the crime of child pornography; 3) find the right model protection to ensure the implementation of children's rights involved the crime of pornography. The type of this research is a normative juridicalstydy (legal research). This study examines the legislation and scientific opinion related criminal policy against child pornography, to realize the guaranteed protection of children's rights crime victims pornography. The results showed that in terms of policies to address the crime of pornography involving children have been accommodated in some particular legislation UU No. 44 of 2008 has set the crime of pornography that explicitly contain child pornography. Even also explicitly criminalize pornography involving children. Besides, in particular also for the protection of children from the influence of pornography and forth in Chapter III of the Child Protection section 15 and section 16, but related to other regulations governing child is UU No. 4 In 1979, UU no. 3 In 1997, UU no. 23 of 2002 . Keywords: Criminal Policy, Children, Pornograph